Effectiveness and Adverse Effects of Tranexamic Acid in Bleeding during Adenotonsillectomy: A Randomized, Controlled, Double-blind Clinical Trial - Fornazieri,Marco Aurélio (2021)
Abstract Introduction Intra and postoperative bleeding are the most frequent and feared complications in adenotonsillectomy (AT). Tranexamic acid (TXA), which is known for its antifibrinolytic effects, has a proven benefit in reducing bleeding in hemorrhagic trauma and cardiac surgery; however, the effectiveness and timing of its application in AT have not yet been established. Objectives We aimed to evaluate the efficacy of TXA in controlling bleeding during and after AT and assess its possible adverse effects in children. Methods The present randomized, controlled, double-blind clinical trial included 63 children aged 2 to 12 years. They were randomly assigned to receive either intravenous TXA (10 mg/kg) or placebo 10 minutes before surgery. The volume of intraoperative bleeding, presence of postoperative bleeding, and adverse effects during and 8 hours after the surgery were assessed. Results No difference in bleeding volume was noted between the 2 groups (mean, 122.7 ml in the TXA group versus 115.5 ml in the placebo group, p = 0.36). No intraoperative or postoperative adverse effects were noted because of TXA use. Furthermore, no primary or secondary postoperative bleeding was observed in any of the participants. Conclusion In our pediatric sample, TXA (10 mg/kg) administration before AT was safely used, without any adverse effects. It did not reduce the bleeding volume in children during this type of surgery. Future studies should assess the use of higher doses of TXA and its administration at other time points before or during surgery.